Sustainable Herbal Hair Tonic for Middle-Aged Health and Wellness - Ridho Iswandi; Usep Suhud (Economic, Management, Business and Accountancy International Journal, 2025)
In order to address hair health issues associated with aging and hormonal decline, this study investigates the creation of a natural hair tonic for individuals between the ages of 40 and 60. The purpose of the study is to evaluate how well herbal compounds, such as ginseng, aloe vera, and rosemary, can promote hair growth, strengthen the scalp, and improve general health. The study determines how these key ingredients support blood circulation, follicle nourishment, and DHT hormone regulation through a qualitative examination of scholarly literature and case studies. The results show that a natural hair tonic improves psychological well-being by boosting confidence and self-image in addition to reducing hair loss and strengthening hair structure. Additionally, by providing a safe and environmentally friendly substitute for items based on chemicals, this innovation advances Sustainable Development Goal (SDG) 3. According to the study's findings, using herbal formulations in the manufacturing of hair tonics has advantages for the environment and human health, making it a smart move for middle-aged people' overall wellbeing.